Batuhampar Trading Village: A Prototype of Halaqah in 19th Century Minangkabau - Apria Putra; Iswantir; Bambang Trisno (Islam Transformatif : Journal of Islamic Studies, 2024)
Abstract This article investigates Batuhampar Trading Village as a prototype of an ideal halaqah system in 19th-century Minangkabau. Established by Sheikh Abdurrahman Batuhampar, the village was a center of Islamic scholarship focusing on Quranic recitation (tilawah), Quranic readings (qira'at al-Qur’an), and the Naqshbandi Khalidiyah Sufi Order. The objectives of this article are (1) to describe the halaqah education system implemented in Batuhampar Trading Village, (2) to identify factors supporting the sustainability of halaqah in Batuhampar Trading Village during the 19th century, and (3) to analyze the scholarly network of Batuhampar Trading Village within the context of Minangkabau intellectualism. The analytical method employed is social intellectual history. The findings indicate that: (1) Batuhampar Trading Village implemented a prominent halaqah system of its time, encompassing Qur'anic halaqah and sufi orders, functioning as a significant scholarly hub; (2) Its success was bolstered by the persuasive preaching of Sheikh Batuhampar, his respected scholarly authority, and the spiritual depth of the village; and (3) Batuhampar Trading Village was founded on a broad scholarly foundation and a cosmopolitan network.   Abstrak Artikel ini menginvestigasi Kampung Dagang Batuhampar sebagai prototipe sistem halaqah ideal di Minangkabau abad ke-19. Kampung Dagang, didirikan oleh Syekh Abdurrahman Batuhampar, merupakan pusat keilmuan Islam yang fokus pada ilmu tilawah, qira’at al-Qur’an, dan Tarekat Naqsyabandiyah Khalidiyah. Tujuan artikel ini adalah: (1) untuk menggambarkan sistem pendidikan halaqah yang diterapkan di Kampung Dagang Batuhampar; (2) untuk mengidentifikasi faktor-faktor yang memfasilitasi keberlanjutan halaqah di Kampung Dagang Batuhampar selama abad ke-19; dan (3) untuk menganalisis jaringan keilmuan Kampung Dagang Batuhampar dalam konteks intelektualisme Minangkabau. Metode analisis yang digunakan adalah sejarah sosial intelektual. Hasil penelitian menunjukkan bahwa: (1) Kampung Dagang menerapkan sistem halaqah yang terkenal pada masanya, yang mencakup halaqah al-Qur’an dan Tarekat, serta berfungsi sebagai pusat keilmuan yang signifikan; (2) keberhasilan Kampung Dagang didukung oleh dakwah persuasif Syekh Batuhampar, kepemimpinan spiritual yang kuat, dan fondasi spiritualitas yang mendalam; dan (3) Kampung Dagang Batuhampar dibangun di atas dasar keilmuan yang luas dan jaringan yang kosmopolitan.